PERAN KEPEMIMPINAN ADAPTIF DALAM PENGUATAN EKOLOGI MADRASAH BERBASIS PENDIDIKAN ISLAM - Muzhir Ihsan; Ima Rahmawati; Hadi Dafenta S; Titin Rustini (Institut Agama Islam Sahid (INAIS) Bogor, 2026)
This study aims to examine the role of adaptive leadership in strengthening ecology based on Islamic education in public Islamic junior secondary schools (Madrasah Tsanawiyah Negeri) in Bogor City. The global ecological crisis requires madrasahs to play a strategic role in supporting sustainable development agendas, particularly SDG 4 on quality education, SDG 13 on climate action, and SDG 16 on effective and accountable institutions. This research employed a quantitative explanatory approach using a survey method involving 125 teachers selected through proportionate random sampling. The research instruments measured adaptive leadership and madrasah ecology, which were statistically analyzed to determine the strength of relationships between variables. The findings indicate that adaptive leadership has a positive and significant effect on strengthening madrasah ecology, with a moderate explanatory power of the model. These results highlight that principals’ capacity to manage change, empower human resources, and integrate Islamic values into institutional governance significantly contributes to the development of sustainable, environmentally oriented madrasah management aligned with the Ministry of Religious Affairs’ strategic priorities.